Scalometry and the Pauline Epistles - Barr, George K. (Journal for the study of the New Testament / Supplement series, 2004)
The book brings insights from the creative arts to the study of New Testament structures. 'Scale' is well known and understood in creative arts such as architecture, sculpture and music, but New Testament scholars have given no significant consideration to scale changes in the Biblical texts. A robust methodology allows scale changes in literature to be examined scientifically and reveals 'scale-related' patterns in the epistles